The Influence of Management Information Systems and Organizational Support on Principal Competence Through Transparency as a Mediating Variable in Public Junior High Schools of Sub-District 6, Pandeglang Regency - Marpuah; B.Herawan Hayadi (Journal of Education and Teaching Learning, 2026)
The competence of school principals is a key determinant of the quality of school management, yet performance appraisal data from several public junior secondary schools in Pandeglang Regency still shows unsatisfactory results. This study aims to examine the effect of management information systems and organizational support on principal competence, both directly and through transparency as a mediating variable. A quantitative explanatory survey design was applied to 144 civil servant teachers from 24 public junior secondary schools in Sub Region 6 of Pandeglang Regency, selected through proportionate stratified random sampling. Data were collected using a Likert scale questionnaire and analyzed with Partial Least Square Structural Equation Modeling. The results show that management information systems and organizational support have a positive and significant effect on both transparency and principal competence. Transparency also has a positive and significant effect on principal competence and acts as a partial mediator on both tested paths. The research model explains 71.4 percent of the variance in principal competence. These findings confirm that strengthening school leadership competence becomes more optimal when the use of information systems and institutional support is accompanied by an open and accountable school management culture.